Table of contents and editorial information - Charles E. Bower (Journal of Applied Communications, 1972)
Editorial front matter and table of contents for vol. 55, no. 4 (Oct.-Dec. 1972) of ACE, Ihe official journal of the American Association of Agricultural College Editors.